2006
DOI: 10.1111/j.1365-2934.2006.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost and resource implications of clinical supervision in nursing: an Australian perspective

Abstract: It is suggested that, on average, the cost of giving peer group one-to-one supervision to any nurse represented about 1% of an annual salary. When interpreted as a vanishingly small cap on clinical nursing practice necessary to reap demonstrable benefits, it behoves Nurse Managers to comprehend clinical supervision as bona fide nursing work, not an activity which is separate from nursing work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…Despite this exception, the vast majority of supervisors reported that they struggled to find the time to provide supervision within their existing workloads. The challenge of finding time for supervision is well documented as being a major barrier to effective clinical supervision practice (Dawson et al, 2012;LLoyd et al, 2014;White & Winstanley, 2006) and the current study reflects this frequent finding.…”
Section: Plan)" Brooklynsupporting
confidence: 58%
See 3 more Smart Citations
“…Despite this exception, the vast majority of supervisors reported that they struggled to find the time to provide supervision within their existing workloads. The challenge of finding time for supervision is well documented as being a major barrier to effective clinical supervision practice (Dawson et al, 2012;LLoyd et al, 2014;White & Winstanley, 2006) and the current study reflects this frequent finding.…”
Section: Plan)" Brooklynsupporting
confidence: 58%
“…However, the number of inconsistencies found in the literature makes it difficult to draw firm conclusions (Crow, 2008;White & Winstanley, 2006). In Watkins and Milne's (2014) recent appraisal of the clinical supervision literature, they lament the dearth of process-outcome research, that is, studies that examine "the relationship between what was done and its effect" (p. 683).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Managers refusal to pay time in lieu for attendance (White & Winstanley, 2009). Based on 14 hours of supervision per year, one-to-one, peer supervision the cost of clinical supervision for nurses is 1% of their annual salary (White & Winstanley, 2006). This would be decreased further if supervision was monthly and a group model was implemented.…”
Section: Critical Refl Ection To Generate Shared Understandingmentioning
confidence: 99%